Perdamaian Maluku dalam Tangkapan Layar: Kajian PAK dalam Film Glenn Fredly The Movie sebagai Media Pendidikan Perdamaian - Sekewael, Olive Reny; Hukubun, Monike; Hursepuny, Jelfy L. (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This article has purpose to analyze Theological student about peace after 20 years Conflict in Mollucas, and it has come and package to be a film with its title “Glenn Fredly The Movie.” This research is a qualitative research with interview process that its make theology student who was watching the movie as an informan. Through the interview process and analysis of the answers from the informants, it was found that the understanding of peace is still greatly influenced by the values instilled by the parents and also the condition of the segregation and the direct experience of the informants. In addtion, the results of the analysis also show that the materials that contain the concept of peace, whether its is about differences and concrete matters in it, are not so covered in the teaching materials of the Churchs Forman Education (PFG). Therefore, learning media such as film and the like can be used to enrich PFG Teaching Materials to build the concept of peace, especially through Christian Religiuous Education, whether i tis materials, media, or methods.